Eggs of the Blind Snake, Liotyphlops albirostris, Are Incubated in a Nest of the Lower Fungus-Growing Ant, Apterostigma cf. goniodes. (15th February 2012) - Bruner, Gaspar; Fernández-Marín, Hermógenes; Touchon, Justin C.; Wcislo, William T.
Abstract : Parental care is rare in most lower vertebrates. By selecting optimal oviposition sites, however, mothers can realize some benefits often associated with parental care. We found three ovoid reptilian eggs within a mature nest of a relatively basal fungus-growing ant, Apterostigma cf. goniodes (Attini), in central Panama. In laboratory colonies, A. cf. goniodes workers attended and cared for the eggs. Two blind snakes, Liotyphlops albirostris (Anomalepididae), successfully hatched, which is the first rearing record for this species. The ants did not disturb the snakes, and the snakes did not eat the ants; we found no ants in the dissected stomachs of the snakes. We review other associations between nesting fungus-growing ants and egg-laying vertebrates, which together suggest that attine nests may provide a safe, environmentally buffered location for oviposition, even in basal attine taxa with relatively small colony sizes.